2009
DOI: 10.1111/j.1447-0756.2008.00990.x
|View full text |Cite
|
Sign up to set email alerts
|

Criteria‐based audit to improve women‐friendly care in maternity units in Malawi

Abstract: The criteria-based audit was associated with an improvement in the quality of women-friendly care services in maternity units in Malawi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Variables with the lowest mean scores on the SCCS were mainly concerned with women's perceptions of care they received during labour and birth, such as help from doctors, midwives or nurses, provision of information and involvement in decision-making regarding their care. This is consistent with findings of previous studies which reported that women were more likely to be satisfied with their care if they had access to unbiased information, involved in making decisions concerning interventions, felt respected and confident that the right treatment and care would be provided (Kongnyuy et al 2009;Waldenström et al 2006). Support and continuity of care have been found to be effective in decreasing women's need for analgesia, reducing the length of labour, accelerating the mothers' recovery, improving maternal-infant bonding and increasing maternal satisfaction (Abdel Ghani & Berggren 2011;Hodnett et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Variables with the lowest mean scores on the SCCS were mainly concerned with women's perceptions of care they received during labour and birth, such as help from doctors, midwives or nurses, provision of information and involvement in decision-making regarding their care. This is consistent with findings of previous studies which reported that women were more likely to be satisfied with their care if they had access to unbiased information, involved in making decisions concerning interventions, felt respected and confident that the right treatment and care would be provided (Kongnyuy et al 2009;Waldenström et al 2006). Support and continuity of care have been found to be effective in decreasing women's need for analgesia, reducing the length of labour, accelerating the mothers' recovery, improving maternal-infant bonding and increasing maternal satisfaction (Abdel Ghani & Berggren 2011;Hodnett et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with findings of previous studies which reported that women were more likely to be satisfied with their care if they had access to unbiased information, involved in making decisions concerning interventions, felt respected and confident that the right treatment and care would be provided (Kongnyuy et al. ; Waldenström et al. ).…”
Section: Discussionsupporting
confidence: 91%
“…The majority of audit and feedback based strategies did not involve large monetary investments, but instead enabled facilities to make the most of their existing resources [22,23,25-27,29-34]. Leigh et al [50] note that locally suggested equipment substitutions reduced costs and allowed for quicker implementation of new procedures due to easier procurement processes.…”
Section: Resultsmentioning
confidence: 99%
“…These women were also less likely to receive epidural anesthesia, with no differences noted in the second stage of labor or in the mode of delivery and no impairment of maternal and fetal well-being (18) . In a study conducted in 29 hospitals in Malaysia with 280 women, 79.3% of the women were informed about the positions for childbirth, and 83.4% chose a position other than supine (19) . The present study revealed that most women in the SBC adopted the semi-sitting position during the second stage of labor.…”
Section: Category Amentioning
confidence: 99%